Vegetable Oil Based Nanoclay Composites - Abul, Hasnat; Abdul, Moheman; Showkat, Ahmad Bhawani; Khalid M., Alotaibi (Springer Nature Singapore Pte Ltd., 2024)
Attempts have been made to replace the non-renewable resources with renewable resources in the development of various signicant materials for a wide range of applications. Vegetable oils are a reasonably abundant resource that is relatively inexpensive around the world. It also has several amenable functional groups that can be used as reaction sites. In this section, efforts have been made to present various types of vegetables and their physico-chemical parameters, as well as various reactive sites for derivatization to various useful polymers. Furthermore, the incorporation of nanoclay materials has been shown to signicantly improve polymer performance when compared to pristine polymer of the same vegetable oil. Nanoclay modied epoxy, polyurethane, poly(ester-amide) and poly(ester) were also included in the text to demonstrate the importance of nanoclay polymers of vegetable origin.